Methodology of Formation of students' Professional Competence Based on Innovative Approach - Khamidullaevna, Karimova Feruza; Muhabbat, Hakimova (Bumi Publikasi Nusantara, 2024)
The article presents a theoretical analysis of the formation of the professional competence of the students of higher education institutes. The principles of intercommunication of its applied character and dynamics for the development of modern society are revealed. It is emphasized that the professional development of the personality is a key issue of modernization of the educational system. The main aim of the system of modern education is to prepare professionally competent specialists in the process of learning, which is carried out based on aims and tasks defined by the requirements of social conditions of the market economy to the system of education and personality as a whole, personal interests and by the system of higher professional education. To be master in the key competencies by students of higher education institutes occurs at inter-active learning of disciplines within technologies of personality-oriented educational approach. The revealing of the efficiency of the process of forming professional competence is carried out through a complex estimation of the achievements of the students, let to determine the level of the formation of key competencies in the students of higher education institutes. For all this, innovating gauges and traditional methods on the basis are used, based on which assess cognitive, motivating-valuable, and activity components of competencies. The result of formulated tenets of the provisions in the formation of key competencies of the students of higher professional education at all levels of cognition, which allow the individual to adapt to the rapidly changing conditions of the market economy and provide the opportunity for personal and professional growth.